2011
DOI: 10.1124/mol.111.071555
|View full text |Cite
|
Sign up to set email alerts
|

The Diamidine Diminazene Aceturate Is a Substrate for the High-Affinity Pentamidine Transporter: Implications for the Development of High Resistance Levels in Trypanosomes

Abstract: African trypanosomiasis is a disease of humans and livestock in many areas south of the Sahara. Resistance to the few existing drugs is a major impediment to the control of these diseases, and we investigated how resistance to the main veterinary drug diminazene aceturate correlates with changes in drug transport in resistant strains. The strain tbat1(Ϫ/Ϫ), lacking the TbAT1/P2 aminopurine transporter implicated previously in diminazene transport, was adapted to higher levels of diminazene resistance. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 32 publications
(57 reference statements)
3
40
0
Order By: Relevance
“…since Babesia parasites multiply asexually with a reproductive time of around 10 hr under normal in vitro culture conditions [27], the genes related to Da resistance would be transferred successfully during multiplication of the parasites; however, we could not determine whether the parasites developed resistance to Da or that the Da-resistant parasites were selected from a mixed population of parasites in the present study. a similar phenomenon has also been reported in Da-resistant Trypanosoma brucei brucei [11,26] and pentamidine-resistant Leishmania species [21] in vitro.…”
Section: Analysis Of Gene Transcription Of Coxi Coxiii and Cytb In supporting
confidence: 49%
See 1 more Smart Citation
“…since Babesia parasites multiply asexually with a reproductive time of around 10 hr under normal in vitro culture conditions [27], the genes related to Da resistance would be transferred successfully during multiplication of the parasites; however, we could not determine whether the parasites developed resistance to Da or that the Da-resistant parasites were selected from a mixed population of parasites in the present study. a similar phenomenon has also been reported in Da-resistant Trypanosoma brucei brucei [11,26] and pentamidine-resistant Leishmania species [21] in vitro.…”
Section: Analysis Of Gene Transcription Of Coxi Coxiii and Cytb In supporting
confidence: 49%
“…indeed, the proliferation potential of the Da-resistant B. gibsoni isolate was lower than in the wild-type in the present study; however, from the present results, it is suggested that the expression of COXI, COXIII, and CYTb in the Da-resistant B. gibsoni isolate was not altered or suppressed by exposure to Da. The possibility of specific mitochondrial changes being involved in DA resistance in african trypanosomes has also been anticipated by Teka et al [26]. Therefore, a further study of energy metabolism, such as glycolysis pathway, Tca cycle, and electron transport system, in the Da-resistant isolate could elucidate the mechanisms of Da resistance and the mechanisms of action of Da against B. gibsoni.…”
Section: Analysis Of Gene Transcription Of Coxi Coxiii and Cytb In mentioning
confidence: 99%
“…The selective pressure associated with widespread drug use, including mass pentamidine chemoprophylaxis in the 1940s, could have contributed to the selection and spread of MPXR parasites (17,34,41). AT1 has been found to be mutated, deleted, or down-regulated in melarsoprol-resistant trypanosomes (10,42) but AT1 knockout generated cells with only a twofold increased resistance to both melarsoprol and pentamidine (14), and there is evidence for resistance that is independent of AT1 disruption (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The P2 aminopurine transporter plays a predominant role in the uptake of aza analogues of furamidine into T. b. brucei s427 trypanosomes (45). The limited cross-resistance of DB829 to pentamidine is presumably because different transporters (41,46)-in addition to P2-are involved in drug uptake of both pentamidine and melarsoprol but do not transport DB829. The existence of less efficient transporters in the T. b. gambiense strains may also explain the observed lower in vitro potency of DB829 against these parasite strains.…”
Section: Discussionmentioning
confidence: 99%